Tingkatkan Efsiensi Produksi dan Pemasaran Gula Semut pada Kelompok Puji Lontar Berbasis Teknologi IoT - I Gusti Lanang Wiratma; Bagus Gede Krishna Yudistira; I Dewa Gede Anom Jambe Adnyana; I Ketut Andika Pradnyana (Universitas Pendidikan Ganesha, 2026)
The “Puji Lontar” palm sugar business group in Tianyar Barat Village, Kubu District, Karangasem Regency, Bali Province, still faces traditional drying methods that depend on the weather, resulting in uneven product moisture content and difficulty meeting market standards (maximum 3%). Downstream, sales are still predominantly conventional (price around IDR 12,000 per ¼ kg), packaging and branding are not yet strong, and financial records and business planning have not been developed. This community service program aims to improve production efficiency and marketing performance through the implementation of IoT drying technology, accompanied by digital marketing training and strengthening MSME management. The activity was carried out for eight months through stages of preparation, socialization, training, mentoring, and evaluation; materials included equipment operations and maintenance, packaging and brand identity, creation of marketplace/website/social media accounts, as well as recording daily transactions and preparing business plans/capital proposals. The evaluation results showed that partners were able to operate the drying technology independently, the drying process was more controlled so that the product moisture content could be maintained below 3%, and the digital marketing strategy drove an increase in turnover of around 25%. This program strengthens the competitiveness of palm sugar MSMEs while supporting the achievement of higher education IKU and SDGs.